Avaliação da função cardíaca do teleósteo neotropical matrinxã, Brycon amazonicus: uma análise matemática e biomolecular - Rivaroli, Luciano (2011)
The ventricular myocardial contractility of the matrinxã teleost, Brycon amazonicus, was analysed in previous experimentation with isometric multicellular preparations, in time effect and force-frequency relationship experiments, with and without exposure to the alkaloid ryanodine, a sarcoplasmic reticulum (SR) Ca2+ release blocker. In this study, different methodological approaches were used, such as isometric stress (EI, mN.mm-2), that permitted to identify the sensitivity of the myocardium to ryanodine, with the majority contribution of Ca2+ from the SR. The use of time to peak tension and time to half relaxation parameters (TPT and THR, ms) were ineffective to evaluate the contraction and relaxation performances during time effect experiments. New approaches such as contraction rates and initial relaxation rates (TC and TIR, mN.mm-2.s-1) demonstrated directly the impairment of the myocardium exposed to ryanodine. The negative staircase effect, characteristic of the teleost s forcefrequency relationship was evidenced by EI. The maximum rates of contraction and maximum rates of relaxation (TMC and TMR, mN.mm-2.s-1) and the average rates of contraction and average rates of relaxation (TMedC and TMedR, mN.mm-2.s-1) showed the impairment of the myocardium contractility exposed to ryanodine as well as the low sensitivity of frequency increments on the contractility when considered the values of TPT and THR. The TMedC and TMedR values indicated a greater possibility of heart rate regulation than the TMC and TMR values, probably due to these estimates consider the amount of instantaneous rate changes of contraction wave on calculation instead of just one point on the curve. The cardiac pumping capacity (CBC, mN.mm2.min-1) showed that the optimal range of frequency for isometric contraction is narrow and that the myocardium of the species should be working on the limit at rest. The analyses of integral of isometric tension (ITI, mN.mm- 2.s), and integral of isometric tension per minute (ITIPM, mN.mm-2.min), showed that these were unsuitable indexes for the assessment of cardiac contractility in the way they were calculated, as inconsistent interpretations were generated, probably by using information from the curve of contraction irrelevant to the isometric preparation. The contractility index (IC, mN.mm-2) created in this work, suggested that the myocardium contractility of the species is more sensitive to increases in frequency. On the other hand, the contractility index per minute (ICPM, mN.mm-2) showed that the optimum range of frequencies for the B. amazonicus myocardial contraction can be much wider and could allow performance reserve, such as reported in other studies of cardiac function in teleosts. The protein expression of SERCA2a and phospholamban (PLB) were analysed by Western Blot technique and their expression supported the findings of the SR functionality. The comparative analysis of these proteins, using amino acid sequences available in public databases (GenBank and UniProt), revealed levels of similarity between the SERCA2a and PLB in fish and other vertebrates, strengthened the findings of studies with Western Blot experiments. Taken together, the results suggest that B. amazonicus myocardium is dependent on SR Ca2+ stores under physiological frequencies and, despite the negative staircase pattern, must possess a performance reserve at supraphysiologic frequencies.